Why digital goods have not replaced traditional goods: the case of e-books. Issue 3 (22nd May 2020) - Kim, Jongbum; Seo, Jeonghun; Zo, Hangjung; Lee, Hwansoo
Abstract : Purpose: Electronic books (e-books) have been in the market for decades but have been unable to replace paper books. Previous studies on e-books have failed to identify significant factors affecting the adoption and diffusion of e-books. This study develops a theoretical framework to explain the adoption behavior of e-books from the perspective of user resistance. Design/methodology/approach: After a pilot test with 50 e-book users, the research model is validated using a partial least squares structural equation modeling (PLS-SEM) technique. A web-based survey method is used to collect data from a sample of 350 people – selected from Korean e-book users and nonusers – during a week in March 2017. This study tests the reliability and validity of the integrated model of planned behavior and resistance theory and tests the hypotheses with bootstrapping resampling. Findings: The results show that four barriers – usage, value, risk and image – cause resistance to change and users with higher resistance have lower intention to use. The moderating effect of self-efficacy between resistance to change and intention to use is confirmed. Self-efficacy interacts not only with the encouraging factors but also with resistance. Originality/value: This study expands the understanding of users' adoption behavior of e-books by examining inhibiting factors using a novel integrated model. The findings of this research provide insights for digital product providers, especially e-book publishers, to understand why digital products have not been successful in the marketplace.